Cognitive rehabilitation in the elderly: A randomized trial to evaluate a new protocol. - ROBERTSON, IAN (Cambridge University Press, 2007)
This study provides an introduction to, and overview of, several papers that resulted from a randomized control trial that evaluated a new cognitive rehabilitation protocol. The program was designed to improve general strategic abilities in ways that would be expressed in a broad range of functional domains. The trial, which was conducted on a sample of older adults who had experienced normal age-related cognitive decline, assessed performance in the following domains: memory, goal management, and psychosocial status. The general rationale for the trial, the overall experimental design, and the approach to statistical analyses that are relevant to each paper are described here. The results for each functional domain are reported in separate papers in this series (JINS, 2007, 13, 120?131.)
PUBLISHED
Keywords: Aging; Memory; Treatment outcome; Cognition; Frontal lobe; Neuropsychology